The Primary Noise Control in the Work Environment by Increasing the Quality of Bearings and Effective Mounting of Machines - ŽIARAN, Stanislav; ŠOOŠ, Ľubomír; CHLEBO, Ondrej (Archives of Acoustics, 2020)
Implementation of European directives is closely related to the quality of production and the associated operational safety, maintenance of machines and mechanical systems, both mobile or stationary, in order to reduce the dynamic load (vibration and noise) on the working environment, not only during their operating state but also during their design, production, and setting of the vibration isolation components. Reducing the dynamic load of mechanical systems and their components is reflected in the working environment by reduced emissions and immissions of noise and vibration. The presented paper investigates the methods and conditions for noise and vibration control, focusing mainly on increasing the quality of rotating machine components, such as bearings by means of effective vibration isolation of the machines. The solution of this problem requires theoretical analysis and methodology for the measurement of the mechanical systems involved. The results of the vibroacoustic measurements were analysed in terms of the low frequency vibration and noise level (quality) of bearings and conditions for effective vibration isolation of the machines using vibroacoustic diagnostic method. Furthermore, the impact on the working environment was also analysed. Finally, the paper suggests some actions to be taken to effectively reduce the unwanted vibrosound energy in working places, also using recycled material as a vibration isolation element.